The Results of Hearing Screening at the Children ith Down Syndrome Andijan Region f Uzbekistan (Global Journal of Medical Research, 2022)
This article presents the primary results of targeted hearing screening among children with Down syndrome, as one of the most common pathologies at risk of developing various forms of hearing loss. As a result of the screening according to the data of delayed otoacoustic emission and otoacoustic emission distortion product, out of the total number of children in 41.5% of cases, objective tests showed the presence of auditory dysfunction, i.e. the answer is "refer". Thus, we found it expedient to carry out hearing screening in children with Down syndrome in order to prevent hearing loss, and secondary forms of delayed psychoverbal development associated with it.
Keywords: down syndrome; auditory screening; hearing loss; children with down syndrome; objective methods of audiometry